2020
DOI: 10.1093/ndt/gfaa314
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease is a key risk factor for severe COVID-19: a call to action by the ERA-EDTA

Abstract: Diabetes, hypertension and cardiovascular disease have been listed as risk factors for severe coronavirus disease 2019 (COVID-19) since the first report of the disease in January 2020. However, this report did not mention chronic kidney disease (CKD) nor did it provide information on the relevance of estimated glomerular filtration rate (eGFR) or albuminuria. As the disease spread across the globe, information on larger populations with greater granularity on risk factors emerged. The recently published OpenSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
180
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 299 publications
(203 citation statements)
references
References 26 publications
16
180
2
5
Order By: Relevance
“…The odds of mortality in these comorbid conditions are provided in Table 1 , comparable with the meta-analysis conducted by Kumar et al 17 . Hazard ratios associated with Chronic Kidney Disease (3.04, CI 1.72–5.38) (Prevalence 6.2%) shows the higher associated risk with comparable results from ERA-EDTA Council and the ERACODA Working Group 18 . The prevalence of Chronic Liver Disease (3.95, CI 1.16–13.42) was comparatively lower than other comorbidities, and hence hazard ratio is higher than other studies 19 .…”
Section: Discussionsupporting
confidence: 61%
“…The odds of mortality in these comorbid conditions are provided in Table 1 , comparable with the meta-analysis conducted by Kumar et al 17 . Hazard ratios associated with Chronic Kidney Disease (3.04, CI 1.72–5.38) (Prevalence 6.2%) shows the higher associated risk with comparable results from ERA-EDTA Council and the ERACODA Working Group 18 . The prevalence of Chronic Liver Disease (3.95, CI 1.16–13.42) was comparatively lower than other comorbidities, and hence hazard ratio is higher than other studies 19 .…”
Section: Discussionsupporting
confidence: 61%
“…Patients with CKD are highly susceptible to COVID-19 and are at an increased risk of progression to a severe or critical form of the disease because of impaired immunity; additionally, they are at enhanced risk of SARS-CoV-2 infection due to frequent hospital attendance [ 2 , 13 , 14 , 15 , 16 , 17 , 18 ]. The prevalence of CKD in patients with COVID-19 has been reported in a wide range of approximately 1–47%; however, it is suggested that the lowest values result from underestimation [ 16 , 19 , 20 , 21 ]. Among patients with COVID-19 hospitalized in 30 Polish centers included in the current analysis, nearly 20% were diagnosed with CKD, of which 18% presented severe renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…We predefined potential baseline confounders, such as age, sex, and concomitant diseases that potentially enhance the risk of severe COVID-19 illness [18] , [19] , [20] .…”
Section: Methodsmentioning
confidence: 99%